Sexist Expressions in Nyakyusa - Saimon, Musa (Issues in Language Studies, 2020)
The way people use language determines and (or) reflects their experience in their social context; the use of everyday language becomes a lens through which people behave and see their world and at other time it is the social practices that influence certain choices of language used by community members. For that reason research on how languages affect women’s image in different speech communities is highly needed for the sake of saving women’s face. This brought to the attention the concept of language and gender in applied linguistics whose focus is on how language use and labelling is associated with gender differences. And those language forms that show gender bias are known as sexist expressions. Drawing on the above scenario, the present study explores sexist expressions in Nyakyusa language using data collected from four Nyakyusa speaking people as key informants through mobile phone interviews. Data were analysed thematically in which I generated themes from coded and categorised data. Findings show that Nyakyusa exhibits elements of sexism through five forms of sexist expressions namely referential gender, social gender, lexical gender, proverbs and idioms and agreements. The researcher calls for creation of awareness among Nyakyusa speech communities for reformation of sexist expressions.